Prevalência de hipotensão ortostática em sessenta idosos hospitalizados nos hospitais-escola HUJBB e FSCMPA na cidade de Belém-Pará - MIRANDA, Dellana Garcia Tavares de (2022)
Orthostatic Hypotension (HO) is important cause of morbidity and mortality, over all in the geriatrical population. Carried through studies indicate that the HO has raised prevalence in elderly, being still today pathology little valued. In this way, they objectify the authors, in descriptive prospective study, to search the prevalence of HO, as well as possible factors related to the illness, in aged hospitalized. They had been evaluated 60 aged interned in two hospital school, being these HUJBB and FSCMPa, of 60 years or, more capable to adopt the ortostática position. After the permanence of each patient per thirty minutes in rest, was verified the sistolic and diastolic pressures in three situations, being with the lying patient and with the patient in stand position after one minute and three minutes prevalence of HO of 35% was found, having as more frequent symptom giddiness when moving itself of the lay down to stand. The illnesses associates had more frequently been arterial hypertention, congestive heart failure and diabetes mellitus. It is concluded to be of great value the regular research of HO in the aged sick person.